2015
DOI: 10.1001/jamapsychiatry.2014.1763
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use in the United States

Abstract: enzodiazepines are widely used in the treatment of anxiety and sleep problems. 1-3 The efficacy of benzodiazepines surpasses placebos in controlling a range of anxiety symptoms 4,5 and reducing the onset of sleep latency. 6 Although practice guidelines recommend newer antidepressants in place of benzodiazepines as first-line treatments for anxiety disorders, 7 there is no evidence for the superior short-term efficacy of antidepressants for anxiety disorders. 8 Moreover, practice guidelines recommend that initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
479
7
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 627 publications
(567 citation statements)
references
References 70 publications
45
479
7
17
Order By: Relevance
“…27,35 This study's observation that 12.1% of people ≥65 years old were prescribed one or more B&Zs, that is, one in four of the care home population and one in nine of the non-care home residents, with care home residents approximately three times more likely to have a B&Z prescribed, is also comparable to the wider literature, 2,25,[27][28][29]37 but is lower than that found among a Canadian sample. 1 This study found anxiolytic prescribing for non-care home residents to be comparable with previous studies.…”
Section: Comparison With Existing Literaturesupporting
confidence: 65%
See 1 more Smart Citation
“…27,35 This study's observation that 12.1% of people ≥65 years old were prescribed one or more B&Zs, that is, one in four of the care home population and one in nine of the non-care home residents, with care home residents approximately three times more likely to have a B&Z prescribed, is also comparable to the wider literature, 2,25,[27][28][29]37 but is lower than that found among a Canadian sample. 1 This study found anxiolytic prescribing for non-care home residents to be comparable with previous studies.…”
Section: Comparison With Existing Literaturesupporting
confidence: 65%
“…However, more personalised data are available for health boards and approved researchers. As with other studies of this nature, the lack of information on drug indications linked to prescribing is a limiting factor, 1,2,[27][28][29]35 but details of prescription indications in patients' clinical notes are known to be incomplete or lacking. 24 This may improve with the introduction of the Scottish Primary Care Resource (SPIRE), a collaboration between the Scottish Government and NHS National Services Scotland to simplify and standardise the process for extracting data from GP practice systems for audit, disease surveillance, benchmarking, planning, and research.…”
Section: Lormetazepam (S) or Zaleplon (S)mentioning
confidence: 99%
“…The rate at which patients received benzodiazepine prescriptions in the Ong et al study 1 (5.1 % of total patients) is similar to that in a recent study by Olfson et al, 6 which estimated that 5.2 % of adults in the United States in 2008 received prescriptions for benzodiazepines. Interestingly, Olfson et al found that most benzodiazepine prescribing was done by non-psychiatrists.…”
supporting
confidence: 81%
“…Given that the study by Olfson et al 6 suggests that the highest rates of benzodiazepine use were among 65-to 80-year-olds, Ong et al's study excludes an important sub-population that may be at greater risk for overlapping benzodiazepine prescriptions, and may underestimate the potential effects of medical comorbidities. Moreover, in light of the indications for benzodiazepines, future studies should include measures of mental health comorbidities.…”
mentioning
confidence: 99%
“…This is concerning, as BZDs and zdrugs are known to have limited long-term therapeutic benefits, and also have adverse consequences for patients, such as dependency, daytime sedation, cognitive impairment and increased rates of falls and accidents [5]. Despite the risks, use of these drugs is particularly common in older people [7]. In a previous study, we conducted a systematic review and meta-synthesis which identified influences on general practitioner (GP) prescribing of these drugs.…”
Section: Introductionmentioning
confidence: 99%